Of the gaze and its spells (I) (Journal of Parents and Teachers, 1995)
The gaze reflects emotions and psychological states, capable of conveying love and genuine connection. Changes in gaze may indicate shyness, guilt or even medical problems. Lack of eye contact may be a sign of insecurity or vulnerability.
Keywords: emotions; gaze; connection; insecurity